2016
DOI: 10.1001/jamaneurol.2016.3338
|View full text |Cite
|
Sign up to set email alerts
|

Tau Positron Emission Tomographic Imaging in the Lewy Body Diseases

Abstract: IMPORTANCEThe causes of cognitive impairment in dementia with Lewy bodies (DLB) and Parkinson disease (PD) are multifactorial. Tau pathologic changes are commonly observed at autopsy in individuals with DLB and PD dementia, but their contribution to these diseases during life is unknown.OBJECTIVE To contrast tau aggregation in DLB, cognitively impaired persons with PD (PD-impaired), cognitively normal individuals with PD (PD-normal), and healthy persons serving as control participants, and to evaluate the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
176
8
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(203 citation statements)
references
References 51 publications
15
176
8
4
Order By: Relevance
“…The results of these studies indicate that Aβ deposition may be suppressed in PD with Lewy body, but tau accumulation and cognitive dysfunction, which are correlated with tau tangles [32,33], appear even with low Aβ deposition and/or rapidly after deposition in patients with PD. This speculation was supported by a recent study on tau imaging showing that cortical aggregates of tau are common in patients with DLB and PD, even in those with low Aβ depositions [34]. Although future cohort studies on cognitive function and tau imaging in PD without dementia are required, we propose that the curves of Aβ deposition and tau-mediated neuronal injury shift to the right and left, respectively, in the dynamic biomarker model of AD as described by Jack et al [35], with the result that the preclinical stage of asymptomatic cerebral Aβ deposition in PD may be shorter and the symptoms of dementia may appear earlier (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…The results of these studies indicate that Aβ deposition may be suppressed in PD with Lewy body, but tau accumulation and cognitive dysfunction, which are correlated with tau tangles [32,33], appear even with low Aβ deposition and/or rapidly after deposition in patients with PD. This speculation was supported by a recent study on tau imaging showing that cortical aggregates of tau are common in patients with DLB and PD, even in those with low Aβ depositions [34]. Although future cohort studies on cognitive function and tau imaging in PD without dementia are required, we propose that the curves of Aβ deposition and tau-mediated neuronal injury shift to the right and left, respectively, in the dynamic biomarker model of AD as described by Jack et al [35], with the result that the preclinical stage of asymptomatic cerebral Aβ deposition in PD may be shorter and the symptoms of dementia may appear earlier (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Early data from tau imaging studies have reported conflicting findings on the relationships between amyloid deposition, tau deposition, and clinical profile in DLB 36, 37. Other important pathophysiological factors such as the extent and severity of Lewy body pathology remain unquantifiable until postmortem.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical [ 18 F]T807 uptake was higher in the DLB and PD with cognitive impairment than healthy controls with in low-amyloid pathology, and higher uptake was observed in the inferolateral temporal and parietal/ precuneus regions (Gomperts et al, 2016). Tau deposition was more variable in DLB patients and was lower in magnitude and extent in PD with cognitive impairment, whereas PD patients without cognitive impairment showed no evidence for tau deposition (Gomperts et al, 2016).…”
Section: Misfolded Proteinsmentioning
confidence: 98%
“…A recent PET study using [ 18 F]T807 investigated tau deposition in DLB, PD with and without cognitive impairment (Gomperts et al, 2016). Cortical [ 18 F]T807 uptake was higher in the DLB and PD with cognitive impairment than healthy controls with in low-amyloid pathology, and higher uptake was observed in the inferolateral temporal and parietal/ precuneus regions (Gomperts et al, 2016).…”
Section: Misfolded Proteinsmentioning
confidence: 99%